VALUASI EKONOMI FUNGSI HIDROLOGIS CAGAR ALAM RAYA PASI DI KELURAHAN NYARUMKOP KECAMATAN SINGKAWANG TIMUR (JURNAL HUTAN LESTARI, 2025)
One cause of human-induced forest destruction is the lack of understanding of the economic value of forest hydrological functions. One of the hydrological functions of forests is to provide water. To encourage people to protect the forest, they need to be educated about the economic value of the forest water they use daily. Raya Pasi Nature Reserve is a conservation area located in West Kalimantan Province. This area flows tributaries to the Nyarumkop Village area, East Singkawang Subdistrict. This study aims to calculate the economic value of the hydrological function of the Raya Pasi Nature Reserve, providing water for household and irrigation needs in rice paddy production for the community in Nyarumkop Village, East Singkawang Subdistrict. This research was conducted by measuring water discharge and using questionnaires to calculate household water use and irrigation of rice fields. Based on the study's results, the economic value of the hydrological function of Raya Pasi Nature Reserve for household needs is Rp 923,304,000/year. The economic value of the hydrological function of the Raya Pasi Nature Reserve for the needs of irrigation of rice fields for rice production by the community of Nyarumkop Village, East Singkawang Subdistrict is Rp 256,338,600/year. The total economic value of the hydrological function of the Raya Pasi Nature Reserve, based on the summation of the value of household water and the value of rice field water is Rp 1,179,642,600/year. Keywords: Raya Pasi Nature Reserve, Nyarumkop Village, hydrological functions, economic valuation Abstrak Salah satu penyebab kerusakan hutan akibat ulah manusia adalah kurangnya pemahaman tentang nilai ekonomi fungsi hidrologis hutan. Satu di antara fungsi hidrologis hutan adalah sebagai penyedia air. Guna mendorong masyarakat menjaga hutan, mereka perlu diberi pengetahuan tentang nilai ekonomi air hutan yang digunakan sehari-hari. Cagar Alam Raya Pasi adalah kawasan konservasi yang terletak di Provinsi Kalimantan Barat. Kawasan ini mengalir anak sungai ke wilayah Kelurahan Nyarumkop Kecamatan Singkawang Timur. Penelitian ini betujuan untuk menghitung nilai ekonomi fungsi hidrologis Cagar Alam Raya Pasi sebagai penyedia air untuk kebutuhan rumah tangga dan kebutuhan pengairan sawah untuk produksi padi bagi masyarakat di Kelurahan Nyarumkop Kecamatan Singkawang Timur. Penelitian ini dilakukan dengan mengukur debit air dan menggunakan kuisioner untuk menghitung penggunaan air rumah tangga dan pengairan sawah. Berdasarkan hasil penelitian dapat diketahui nilai ekonomi fungsi hidrologis Cagar Alam Raya Pasi untuk kebutuhan rumah tangga yaitu sebesar Rp 923.304.000/tahun. Nilai ekonomi fungsi hidrologis Cagar Alam Raya Pasi untuk kebutuhan pengairan sawah untuk produksi padi oleh masyarakat Kelurahan Nyarumkop Kecamatan Singkawang Timur yaitu sebesar Rp 256.338.600/tahun. Didapati nilai ekonomi total fungsi hidrologis Cagar Alam Raya Pasi berdasarkan penjumlahan dari nilai air rumah tangga dan nilai air sawah yaitu sebesar Rp 1.179.642.600/tahun. Kata kunci: Cagar Alam Raya Pasi, Kelurahan Nyarumkop, fungsi hidrologis, nilai air.